2003
DOI: 10.1186/1471-2474-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the clinical course of musculoskeletal complaints in general practice: design of a cohort study

Abstract: BackgroundMusculoskeletal complaints are frequent and have large consequences for public health. Information about the prognosis after presentation in general practice is far from complete. Knowledge about determinants of the clinical course of musculoskeletal complaints is essential for management decisions and to inform patients about their prognosis. The purpose of this study is to provide information about the prognosis of musculoskeletal complaints other than low back pain by studying the course of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(20 reference statements)
2
19
0
Order By: Relevance
“…Using these data, the course of hip complaints presented in general practice can be described and relevant prognostic indicators of outcome can be identified. The design of the study has been described in further detail elsewhere (19). The study protocol was approved by the Medical Ethics Committee of the VU University Medical Center.…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…Using these data, the course of hip complaints presented in general practice can be described and relevant prognostic indicators of outcome can be identified. The design of the study has been described in further detail elsewhere (19). The study protocol was approved by the Medical Ethics Committee of the VU University Medical Center.…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…49 In this systematic review, these would be the models developed by Belo et al 6 for recovery and the model developed by van der Waal et al 41 for function. For external validation, we were able to use 3 different data sets that included patients with knee pain: the General Practitioners Research Network Erasmus University Rotterdam (HONEUR) cohort, 13 the BAS cohort, 40 and the Cohort Hip and Cohort Knee (CHECK) cohort 47 ; however, all 3 data sets missed 1 or more essential predictors. Also, there were no suitable proxies available in these data sets; therefore, we were not able to externally validate the existing prognostic models.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In developing the new models (in the BAS cohort), 40 we found that the explained variance of the function model was 0.36 and the recovery model was 0.33. The function model demonstrated good performance as a prognostic model, after internal validation, while the recovery model failed to reach our a priori threshold for good model performance.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The musculoskeletal disorder study (MDS) is a large observational cohort study that was conducted in 61 general practices (97 general practitioners) (20)(21). The physicians recruited patients who consulted them due to a new episode of musculoskeletal pain.…”
Section: Musculoskeletal Disorder Studymentioning
confidence: 99%